Desempeño laboral y satisfaccion laboral de los analistas de créditos de la Caja Maynas de la ciudad de Iquitos 2023 - Diaz Sevillano, Jonathan Rivaldo (2024)
In the context of the descriptive research with a quantitative approach conducted to determine the relationship between job performance and job satisfaction of credit analysts at Caja Maynas in the city of Iquitos in 2023, a cross-sectional design was employed, collecting data at a single point in time. The results reveal a significant correlation between the variables under study, job performance, and job satisfaction. The Pearson correlation, with a value of 0.717, indicates a strong and positive connection: as job performance improves, job satisfaction also improves, and vice versa. The statistical significance, with a level of 0.000 for both variables, supports the acceptance of the proposed hypothesis. When calculating the Pearson correlation coefficient for the grouped data in variables 1 and 2, a value of 0.717 was obtained. Furthermore, the sigma value for both sides is 0.000, which is below the critical threshold of 0.05 according to the decision rule. Consequently, it is conclusively concluded that there is a significant relationship between job performance and job satisfaction of credit analysts at Caja Maynas in the city of Iquitos in 2023. These findings suggest the importance of promoting strategies that enhance both performance and job satisfaction, recognizing the vital interconnection between these dimensions for well-being and work effectiveness.